Public Employee Speech and Magarian's Dynamic Diversity - Heidi Kitrosser (Washington University Law Review, 2018)
The Supreme Court under Chief Justice John Roberts has been praised in many quarters as a committed ally of free speech. Certainly, a number of Roberts Court decisions do protect speech. Putting aside the Court’s controversial campaign finance decisions—the merits of which divide even free speech advocates—the Roberts Court’s speech-protective decisions include several cases in which it refused to create new categories of “unprotected” speech, a decision striking a buffer zone around abortion clinics as too restrictive of protests, and a case in which the Court rejected a provision conditioning certain federal funds on recipients’ adopting a particular policy position. While I am mostly very pleased with the Court’s speech-protective decisions, I count myself among those who think that the Court has not, on balance, been a champion of free speech. I take this view in light of the vast deference that the Court has accorded the government to suppress speech in several contexts. These include those in which threats to national security are invoked, those in which the government purports to act as a speaker itself, or those in which the government acts in a managerial role, such as employer, jailer, or educator. This is not a mere matter of tallying free speech wins and losses. My concern is not simply the number of problematic cases, but the importance of the speech that they fail to protect, and the danger of the discretion that they accord the government. For example, Holder v. Humanitarian Law Project impacts core political speech—ranging from the teaching of peaceful international conflict resolution to the writing of amicus briefs to the U.S. Supreme Court—coordinated with a designated foreign terrorist organization (FTO). Despite the FTO label’s ominous ring, courts have been highly deferential toward the government’s designations, just as the HLP Court was deeply credulous in evaluating Congress’ assertions regarding the dangers of coordinated speech. In another pair of cases, the Roberts Court took an expansive view of the speech forums that the government may claim as its own, rather than belonging to the public. In so doing, the Court widened the space—both physical and virtual—in which the government may exclude speakers based on content or even viewpoint. I am not alone, of course, in noticing the anti-speech tenor of many Roberts Court decisions. Others have observed and lamented this reality, as well as the distance between it and the Roberts Court’s reputation as a free speech stalwart. And now, in a terrific new book called Managed Speech: The Roberts Court’s First Amendment, Professor Greg Magarian of the Washington University School of Law adds important new insights to the mix. The Roberts Court, Magarian observes, is committed to “managed speech.” “Managed speech describes a mode of First Amendment jurisprudence that seeks to reconcile substantial First Amendment protection for expressive freedom with aggressive preservation of social and political stability. . . . [It] concentrates managerial power over public discussion in the government or in favored private actors.” From this perspective, it makes perfect sense for the Roberts Court to fiercely protect the government’s ability to control speech within public spaces and government operations. And the Court’s many decisions favoring private speakers for the most part can be explained either as bolstering powerful interests or as very narrowly applying, extending, or qualifying precedent. In contrast to managed speech, Magarian supports an approach that he calls “dynamic diversity,” which “seeks to maximize . . . diversity of ideas” and diversity of speakers in public discussion. We should value dynamic diversity, he explains, because it protects free speech’s role as “an engine of political and social change.” “Dissent lies at the heart of dynamic diversity.”
Keywords: Managed Speech; Dynamic diversity; Public employee speech; Free speech; Roberts Court; First amendment; Coordinated speech; Political speech; Greg Magarian